PROFIL PROTEIN DAGING KAMBING, KERBAU DAN SAPI YANG DIRENDAM LARUTAN JAHE BERBASIS SDS-PAGE - Rieke Fadhila; Sri Darmawati (Universitas Muhammadiyah Semarang, 2017)
Ginger contains protease enzyme and that is Zingibain which can hydrolyze proteins so it can soften meat. The aim of this study is to analyze protein profiles in goat, buffalo and cow meats before and after those meats are soaked with ginger solution in 4% v/v, 6% v/v, 8% v/v and 10% v/v concentrations for 30 minutes. Protein profile of meats was analyzed with SDS-PAGE method. The result of this study shows that control meats which are not soaked with ginger solution have many major protein bands while sample meats which have soaked with ginger solution have many minor protein bands. The result of this study shows thatsoaking meats with ginger solution can soften meats because zingibain enzyme in ginger solution can break peptide bonds in protein of meat so it forms micromolecules (minor bands). Ginger solution which is the best to soak goat, buffalo and cow meats is on 4% concentration because there are so many proteins in those meats. The higher ginger solution concentration is the more and more zingibain enzyme content are so the ability to hydrolize protein is higher marked with slackening major protein bands and increasing minor protein bands. Keywords: Meat, Ginger, Protein Profiles, SDS-PAGE